Efisiensi Anggaran Berdasarkan Inpres No. 1 Tahun 2025 Terhadap Hak Konstitusional Pendidikan Warga Negara - Gufron Ihsan (Jurnal Interpretasi Hukum, 2025)
This study examines the legal issues that arise when Presidential Instruction (Inpres) No. 1 of 2025 on budget efficiency is applied to the education sector. The purpose of this research is to analyze the legal status of the Inpres within the national legal system, assess its compatibility with the principle of distributive justice, and evaluate its impact on the fulfillment of the right to education. This study employs normative legal research. The findings reveal that the Inpres does not constitute a binding legal norm for the general public, making its application problematic when used as the basis for policies affecting fundamental rights. Moreover, the budget efficiency policy implemented through Inpres No. 1 of 2025 has the potential to decrease the quality and accessibility of education, particularly in underdeveloped, frontier, and outermost (3T) regions. This includes reductions in non-permanent teaching staff, stagnation in infrastructure development, and limited educational assistance programs. Viewed through the lens of John Rawls’ theory of distributive justice, the policy fails to uphold the principle of prioritizing the most vulnerable groups.